2017
DOI: 10.1001/jamacardio.2017.2346
|View full text |Cite
|
Sign up to set email alerts
|

Balanced Adoption of Radial Artery Access for Primary Percutaneous Coronary Intervention

Abstract: This Viewpoint discusses the need for determining an optimal balance between femoral and radial artery access in primary percutaneous coronary intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Campelo-Parada et al demonstrated a significantly lower rate of long-term major adverse cardiac events (MACE) in patients undergoing PCI using TRA compared to those with transfemoral access (TFA) 5. Nonetheless, TFA still remains the most commonly used approach because of several potential drawbacks of TRA, e.g., higher frequency of crossover to alternative vascular access, longer procedure time, inability to insert mechanical circulatory support devices, and risk for potential arterial conduits for bypass graft surgery 6.…”
Section: Introductionmentioning
confidence: 99%
“…Campelo-Parada et al demonstrated a significantly lower rate of long-term major adverse cardiac events (MACE) in patients undergoing PCI using TRA compared to those with transfemoral access (TFA) 5. Nonetheless, TFA still remains the most commonly used approach because of several potential drawbacks of TRA, e.g., higher frequency of crossover to alternative vascular access, longer procedure time, inability to insert mechanical circulatory support devices, and risk for potential arterial conduits for bypass graft surgery 6.…”
Section: Introductionmentioning
confidence: 99%